Review of Light the Night - Shuwen Yang (Global Storytelling)
This review offers a brief analysis of Light the Night (2021), including its background, plot, and characters. It also discusses the history of Taiwanese drama and the collaboration between Netflix and Taiwanese talents in the TV industry.